2020
DOI: 10.1177/0194599820951470
|View full text |Cite
|
Sign up to set email alerts
|

The Face of COVID‐19: Facial Pressure Wounds Related to Prone Positioning in Patients Undergoing Ventilation in the Intensive Care Unit

Abstract: In the setting of COVID-19 (coronavirus disease 2019)–associated moderate and severe acute respiratory distress, persistently hypoxemic patients often require prone positioning for >16 hours. We report facial pressure wounds and ear necrosis as a consequence of prone positioning in patients undergoing ventilation in the intensive care unit in a tertiary medical center in New York City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 8 publications
(12 reference statements)
0
19
0
1
Order By: Relevance
“…The global incidence of PUs is up to 42.2% of seriously ill patients with COVID-19 infection who are admitted to the ICU under IMV [ 1 ]. It is interesting to observe the distinctive distribution of PUs in patients with COVID-19, where up to 23.9% occur in areas put under pressure due to prone ventilation, for which the main risk factor is being on IMV in this position for 12 or more hours a day [ 2 , 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The global incidence of PUs is up to 42.2% of seriously ill patients with COVID-19 infection who are admitted to the ICU under IMV [ 1 ]. It is interesting to observe the distinctive distribution of PUs in patients with COVID-19, where up to 23.9% occur in areas put under pressure due to prone ventilation, for which the main risk factor is being on IMV in this position for 12 or more hours a day [ 2 , 3 ].…”
mentioning
confidence: 99%
“…The global incidence of PUs is up to 42.2% of seriously ill patients with COVID-19 infection who are admitted to the ICU under IMV [1]. It is interesting to observe the distinctive distribution of PUs in patients with COVID-19, where up to 23.9% occur in areas put under pressure due to prone ventilation, for which the main risk factor is being on IMV in this position for 12 or more hours a day [2,3]. The complete treatment of PUs is extremely expensive, and can reach USD 561 a day considering medical supplies, surgical management, human resources, and the prolonged hospital stay, which affects the finances of healthcare centers [4].…”
mentioning
confidence: 99%
“…For example, some clinical experts recommend that turning the patient should be executed by trained staff only and that the head should be turned on a regular basis. 2 , 9 Both measures could be trained and improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the worldwide extended prone position ventilation use in the COVID-19 pandemic, there have been rising concerns of its associated adverse events and complications that can be devastating, with their management hampered by the isolation precaution and personal protective equipment scarcity, and also by patient condition [ 12 , 13 ]. Several studies have reported certain complications of prone positioning in COVID-19 patients, including pressure-related skin and scalp ulcers, and facial and ocular injuries [ 14 , 15 ]. However, neurological complications related to prone position were reported as brachial plexus and peripheral nerve compression injuries [ 16 - 19 ].…”
Section: Discussionmentioning
confidence: 99%